RENTAS ECLESIÁSTICAS DEL OBISPADO DE NICARAGUA Y COSTA RICA EN 1704 - Aguirre Salvador, Rodolfo (2011)
In 1699 Pope Innocent I granted to Spanish crown a ecclesiastical subsidy for a million ducats of silver, which had collected 10% of all ecclesiastical revenues of the dioceses of America. Firstly, the orders came to the archbishopric of Mexico and from there forwarded to the suffragan dioceses, then establishing a correspondence between the Archbishop and bishops. This paper presents a letter of 1706, Fray Diego Morcillo, newly appointed bishop of Nicaragua, accompanied by a relationship of ecclesiastical subsidy amount was regulated in the same diocese, 1704. Morcillo Bishop’s letter is addressed to the Archbishop of Mexico, giving an account of the state kept the collection in Nicaragua and Costa Rica, plus some other problems of government of the prelate. The ratio of the income was produced by the collector general of the bishopric, Pablo de la Madriz Paniagua, Sagrario’s oldest priest of the Cathedral of León and curator of the Holy Crusade.